Modeling The Multiple Indirect Effect Among Latent Constructs By Using Structural Equation Modeling: Volunteerism Program - Wan Mohamad Asyraf Wan Afthanorhan (Institute of Advanced Engineering and Science, 2014)
This study aimed to evaluate the factors used for develop a best model of multiple indirect effect among latent constructs by using Structural Equation Modelling (SEM) on volunteerism program as a research subject. The data be collected through questionnaires distributed at four higher education institution. This questionnaire is constructed based on four dimension which is motivation, benefits, goverment support, and barrier The data were distributed by using stratified sampling technique and involving 453 respodents . In this case, the data were analyzed by using Analysis Moment of Structural (AMOS) 18.0 in order to examine the influence of exogenous and endogenous variables. As a result showed that the goverment support is significant and direct influences on motivation, benefits, and barrier. Moreover, the benefits and barrier is significant and direct influence on motivation. In generals, the findings revealed that benefits influence is most crucial for motivation of volunteerism.